ANALISA EFEKTIFITAS PENGGUNAAN ALAT RESUSITASI JANTUNG PARU OTOMATIS PADA PASIEN DENGAN HENTI JANTUNG: TELAAH LITERATUR - Sucipto Dwi Tanda (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
Background: Emergency is a sudden event that requires immediate action. Heart disease is a disease that is still a major problem in the world. Heart disease is a disorder of the circulatory system. Complications resulting from heart disease are cardiac arrest. Automatic CPR tools can help solve problems in reducing the effectiveness of doing CPR manually. The main problem with manual CPR is the helper's fatigue when doing CPR.Objective: This study aimed to examine technology related to the use of automatic CPR devices in patients with cardiac arrest.Methods: This method used literature review. The data was taken from several scientific sources based on PubMed, EBSCOhost, ProQuest, ScienceDirect and Wiley Library Online. This study used criteria and keywords.Result: The use of automatic tools can provide more consistent compression (speed and depth) than manual compression. But AHA did not recommend the use of automatic tools because there was no evidence that automated tools provides better results than manual compression.Conclusion: The assumption of future development was that technological progress in carrying out CPR can automatically increase the effectiveness of the performance of the tool. Keywords : CPR, Automatic, compression too